FEDERALISM IN NIGERIA AND LOCAL GOVERNMENT FINANCIAL AUTONOMY: ATTORNEY GENERAL OF THE FEDERATION VERSUS ATTORNEY GENERAL OF ABIA STATE & 35 ORS (2024) - Linus , Gadzama Christopher; Okeokwo, ThankGod (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The Constitution of the Federal Republic of Nigeria 1999 (as amended) serves as the foundational legal framework for governance in Nigeria, delineating the structure and functions of government at various tiers. General Background: Recent Supreme Court rulings concerning local government autonomy have intensified debates about the nature of Nigeria’s federal structure, particularly regarding whether it constitutes a two-tier or three-tier system. Specific Background: This article critically examines the constitutional provisions that govern local government administration and the legislative authority of State Houses of Assembly, focusing on the implications for Nigeria's federal architecture. Knowledge Gap: While existing literature has addressed aspects of Nigeria’s federalism, there remains limited analysis of the constitutional recognition of local government as a third tier and its dependence on state legislatures. Aims: The objective of this study is to elucidate whether the Nigerian Constitution endorses a two-tier or three-tier federal structure and to assess the implications of recent judicial decisions on local government autonomy. Results: The findings indicate that the Constitution acknowledges a three-tier federal system, with local government councils—despite being the closest to the grassroots—remaining under the legislative control of the states. Novelty: This research contributes to the discourse on Nigerian federalism by highlighting the unique characteristics of local governance within the constitutional framework. Implications: It is recommended that the 1999 Constitution be amended to establish local governments as a fully independent third tier, eliminating their reliance on state governments, thereby enhancing local governance and accountability.